A Utopian Life, Yet Not Antinomian: Abrogation of Sharīʻa and the Qiyāma Doctrine in Ismāʻīlī Thought - Yusuf Sansarkan (Al-Jami'ah Research Centre, 2025)
Early Ismāʻīlī belief describes the advent of the seventh imam as qiyāma. However, this qiyāma does not signify the end of the world. Rather, it marks the end of the era of concealment (satr), which began with the first imam, and the beginning of the era of revelation (kashf). This event is also understood as the moment when the Sharīʻa (Islamic law) will be abolished. Throughout history, certain Ismā’īlī groups have believed that the Qāʼim, the seventh imam, had already appeared and attempted to live a utopian life without Sharīʻa. These beliefs, along with historical experiences associated with them, gave rise to accusations of antinomianism (ibāḥa) against the Ismāʻīlīs. The present study seeks to clarify the Ismā’īlī understanding of the abolition of Sharīʻa by examining the views of prominent missionaries (dāʻī) who may be regarded as the founders of this intellectual tradition. It argues that Ismāʻīlī authors generally agreed that the Sharīʻa would remain in force until qiyāma, after which a period without it would begin.[Dalam keyakinan awal Ismāʻīlī, kemunculan imam ketujuh digambarkan sebagai qiyāma. Namun, qiyāma ini tidak menandakan akhir dunia. Sebaliknya, ia menandai berakhirnya era penyembunyian (satr), yang dimulai sejak imam pertama, serta dimulainya era peningkapan (kashf). Peristiwa ini juga dipahami sebagai saat ketika hukum Islam (Sharīʻa) akan dihapuskan. Sepanjang sejarah, beberapa kelompok Ismāʻīlī meyakini bahwa Qā’im, yaitu imam ketujuh, telah muncul dan berupaya menjalani kehidupan utopis tanpa Sharīʻa. Keyakinan-keyakinan ini, bersama dengan pengalaman historis yang berkaitan dengannya, memunculkan tuduhan antinomianisme (ibāḥa) terhadap kaum Ismāʻīlī. Kajian ini bertujuan untuk memperjelas pemahaman Ismā’īlī mengenai penghapusan Sharīʻa dengan menelaah pandangan para misionaris terkemuka yang dapat dianggap sebagai para perintis tradisi intelektual ini. Kajian ini berargumen bahwa para penulis Ismāʻīlī pada umumnya sepakat bahwa Sharīʻa akan tetap berlaku hingga qiyāma, setelah itu barulah dimulai suatu periode tanpa keberlakuannya.]